Psychological career resources of working adults: A South African survey - Melinde Coetzee (SA Journal of Industrial Psychology, 2008)
The main objective of this study was to explore broad trends regarding how individuals from various age, educational, marital, race and gender groups in the South African organisational context differ in terms of their psychological career resources, as measured by the Psychological Career Resources Inventory. A sample of 2 997 working adults registered as students at a South African higher distance education institution participated in this study. The results indicate significant differences between the various biographical variables and the participants’ psychological career resources. In the context of employment equity, and with more women entering the workplace, this study is expected to contribute important knowledge that will inform career development practices concerned with enhancing employees’ career meta-competencies as an important element of their general employability.